THE EFFECT OF PLYOMETRIC TRAINING VERSUS AEROBIC EXERCISE TRAINING ON BODY MASS INDEX (BMI) AND CARDIOVASCULAR FITNESS IN OVERWEIGHT SCHOOL-GOING ADOLESCENTS: A COMPARATIVE STUDY - Dr. Sonia Bhatia; Dr. Sandipkumar Parekh (The Bioscan, 2026)
Background: Overweight and obesity are characterized by an excessive buildup of fat, which poses significant health hazards, including alterations in body mass index and reduced cardiovascular fitness. These conditions are increasingly prevalent among adolescents and warrant targeted intervention strategies. Aim: This study was designed to assess the comparative effects of plyometric training versus aerobic exercise training on BMI and cardiovascular fitness among overweight adolescents in Anand city. Method: In total, 30 overweight adolescents from schools in Anand, Gujarat, were recruited. Group A underwent plyometric training, while Group B took part in aerobic training. Both groups participated in 16 supervised sessions over four weeks (four sessions per week on non-consecutive days). Pre- and post-intervention assessments included BMI measurements and the Queens College Step Test to evaluate cardiovascular fitness. Results: Group A (plyometric training) showed greater improvements in both BMI and cardiovascular fitness compared to Group B (aerobic training). The mean post-intervention values were 85.38 ± 15.4 for Group A and 76.51 ± 10.52 for Group B, indicating statistically significant improvement in the plyometric group. Conclusion: Plyometric exercise training demonstrated superior efficacy in reducing BMI and enhancing cardiovascular fitness among overweight adolescents compared to aerobic exercise training, suggesting its potential as a more effective intervention strategy in school-based fitness programs. Keywords Plyometric Training, Cardiovascular Fitness, Overweight Adolescents, Obesity Prevention.